Investigation of Processes in the Measuring Part of Digital Devices of Relay Protection in the MATLAB Software Package; Russian Electrical Engineering; Vol. 90, iss. 2 - Andreev M. V. Mikhail Vladimirovich (2019, 2019)
Title screen